2014
DOI: 10.1371/journal.pone.0104673
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis Infection and Occupational Protection among Health Care Workers in Two Types of Public Hospitals in China

Abstract: ObjectiveTo determine the impact factors of latent tuberculosis infection (LTBI) and the knowledge of TB prevention and treatment policy among health care workers (HCWs) in different types of hospitals and explore the strategies for improving TB prevention and control in medical institutions in China.MethodsA cross-sectional study was carried out to evaluate the risk of TB infection and personnel occupational protection among HCWs who directly engage in medical duties in one of two public hospitals. Each poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 13 publications
4
32
2
2
Order By: Relevance
“…We expect that the majority of TB patients among HCW will be detected between screening appointments, and that the screening programme has increased awareness of the need to report symptoms early. Other studies have found that HCW are at 2–4 times increased risk of TB than the general population [16]. We could not confirm this, possibly due to the above mentioned reasons.…”
Section: Discussioncontrasting
confidence: 62%
“…We expect that the majority of TB patients among HCW will be detected between screening appointments, and that the screening programme has increased awareness of the need to report symptoms early. Other studies have found that HCW are at 2–4 times increased risk of TB than the general population [16]. We could not confirm this, possibly due to the above mentioned reasons.…”
Section: Discussioncontrasting
confidence: 62%
“…Our study did not find that HCWs who had worked longer periods in TB facilities were more susceptible to be infected with TB [6, 18, 23]. However, results indicated that HCWs aged 51 years or above were at higher risk of contracting TB, in line with the available literature [24]. This might be due to impaired immunity in older people [25] and higher exposure to TB patients [16].…”
Section: Discussionsupporting
confidence: 71%
“…We hypothesized that this population may be enriched with individuals who made protective humoral responses against Mtb. Healthcare workers (HCWs) in developing world settings have an extremely high exposure to tubercule bacilli because of the lack of appropriate barrier protection and a subsequent raised risk of infection (16,17). We specifically chose to investigate individual responses as opposed to cohort effects because of the experience in the HIV field that showed that protective antibodies were made by only a subset of infected individuals (18).…”
mentioning
confidence: 99%